A novel approach for measuring large magnetic anisotropy energy with a limited magnetic field range - Jeong Yun-Chae; Kim Minhwan; Lee Seong-Hyub; Chang Jun-Young; Choe Sug-Bong; Je Soong-Geun; Kim Duck-Ho (The Korean Physical Society, 2024)
Here we propose an experimental method for determining the magnetic anisotropy field in ferromagnetic materials. Our method involves examining the small-angle variation of spontaneous magnetization by the external magnetic field and interpreting the experimental result within the framework of the Stoner-Wohlfarth model applicable to ferromagnetic materials. This method allows for the extrapolation of magnetic anisotropy fields, even when they surpass conventional measurement limits. As a result, a broad range of magnetic anisotropy fields can be ascertained using a single experimental setup. Our proposed method serves as a versatile tool for analyzing large magnetic anisotropy energy which is an important parameter for future spintronic devices.